2019
DOI: 10.1111/bcp.13845
|View full text |Cite
|
Sign up to set email alerts
|

New steps in infliximab therapeutic drug monitoring in patients with inflammatory bowel diseases

Abstract: AIMSTherapeutic drug monitoring (TDM) of infliximab (IFX) appears to be beneficial for patients with inflammatory bowel disease (IBD). However, the recommended target concentrations depend partly on the method used to quantify IFX. Since we recently developed a liquid chromatography-tandem mass spectrometry method to quantify IFX, we aimed to determine IFX trough concentrations (Cmin) associated with biological remission. METHODSWe retrospectively measured IFX Cmin in sera from 55 patients with IBD, on IFX mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However, the validation of LC-MS methods for infliximab, adalimumab ( Jourdil et al, 2018 ; El Amrani et al, 2019 ), and vedolizumab ( Schulze et al, 2018 ) returned findings significantly correlated with those obtained with ELISA immunoassays. Interestingly, the application of an LC-MS method to infliximab TDM gave a plasma concentration threshold of 6.2 mg/L for biological remission (plasma CRP<5 mg/L and FCP<150 μg/g stools) of the disease ( Nemoz et al, 2019 ), a value that was in the lower band of the therapeutic range suggested for mucosal healing in the maintenance period ( Ungar et al, 2016 ; Yarur et al, 2017 ). In another trial, an LC-MS method did monitor trough levels of vedolizumab in IBD patients ( Schulze et al, 2018 ).…”
Section: Personalized Medicine In Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…However, the validation of LC-MS methods for infliximab, adalimumab ( Jourdil et al, 2018 ; El Amrani et al, 2019 ), and vedolizumab ( Schulze et al, 2018 ) returned findings significantly correlated with those obtained with ELISA immunoassays. Interestingly, the application of an LC-MS method to infliximab TDM gave a plasma concentration threshold of 6.2 mg/L for biological remission (plasma CRP<5 mg/L and FCP<150 μg/g stools) of the disease ( Nemoz et al, 2019 ), a value that was in the lower band of the therapeutic range suggested for mucosal healing in the maintenance period ( Ungar et al, 2016 ; Yarur et al, 2017 ). In another trial, an LC-MS method did monitor trough levels of vedolizumab in IBD patients ( Schulze et al, 2018 ).…”
Section: Personalized Medicine In Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…This monoclonal antibody plays an important role in treatment, as it is indicated to reduce signs and symptoms, to induce and maintain clinical remission and mucosal healing, to reduce or discontinue corticosteroid administration and to reduce hospitalizations. 4 However, the pharmacokinetics of these agents and their immunogenicity imply a loss of response over time, due to the reduction of therapeutic levels of the drug, in addition to the appearance of neutralizing antibodies against the drug. Thus, it was analyzed that higher concentrations of these anti-TNF agents, especially during the induction period of treatment, are associated with better long-term therapeutic responses, such as disease remission and mucosal healing.…”
Section: Introductionmentioning
confidence: 99%